Institutional constraints on Philippine growth. - De Dios, Emmanuel S. (2011)
After a review of the institutional economics literature, time- series evidence is presented to show that recent Philippine economic growth has been hindered by institutional weaknesses. In particular, variables representing political instability and corruption are seen to have significantly affected the investment ratio. A historical analysis traces the origins and persistence of these problems to deeper questions of constitutional legitimacy, unstructured rivalry among elites, and weak support for formal institutions owing to preexisting economic inequality.
Keywords: Corruption -- Economic aspects; Political stability -- Economic aspects; Institutional economics; Economic development -- Social aspects; Economic development -- Political aspects